2004
DOI: 10.1182/blood-2004-03-0901
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of acute lymphoblastic leukemia progenitor cells

Abstract: Only some acute lymphoblastic leukemia (ALL) cells are thought to be capable of proliferating to maintain the leukemic clone, and these cells may be the most relevant to target with treatment regimens. We have developed a serum-free suspension culture (SC) system that supported growth of B-ALL cells from 33 patients for up to 6 weeks. ALL cells from 28 cases (85%) were expanded in this system, and growth was superior in SC than in long-term bone marrow culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
150
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(163 citation statements)
references
References 32 publications
9
150
1
2
Order By: Relevance
“…In addition, it was suggested that ETV6-RUNX1-positive cells capable of reconstituting leukemia upon transplantation to NOD-SCID mice have the CD19 À phenotype. 32 The inhibition of B-ALL cell spreading is likely related to the ability of IL-27 to function directly against tumor cell through inhibition of cell proliferation and angiogenesis, and induction of apoptosis, as supported by our in vitro results. Furthermore, we showed that IL-27 downregulated miR-155 in B-ALL cells.…”
Section: Discussionsupporting
confidence: 67%
“…In addition, it was suggested that ETV6-RUNX1-positive cells capable of reconstituting leukemia upon transplantation to NOD-SCID mice have the CD19 À phenotype. 32 The inhibition of B-ALL cell spreading is likely related to the ability of IL-27 to function directly against tumor cell through inhibition of cell proliferation and angiogenesis, and induction of apoptosis, as supported by our in vitro results. Furthermore, we showed that IL-27 downregulated miR-155 in B-ALL cells.…”
Section: Discussionsupporting
confidence: 67%
“…These data indicate that primitive progenitor cells rather than more committed lymphoid cells are targeted by BCR-ABL gene rearrangement in ALL. A different study used human leukemic cells from patients with other subgroups of ALL 47,48 . ALL cells with a CD34+ CD10-phenotype were capable of transferring leukemia to NOD/SCID mice.…”
Section: Hematopoietic Stem Cells As Targets Of Transforming Mutationmentioning
confidence: 99%
“…However, in the acute leukaemic phase of CML or in P190-B-ALL, imatinib treatment is not effective (Shah et al, 2002). The origin of CML and p190-B-ALL begins in a haematopoietic stem cell (HSC), a target population that is largely quiescent (Cobaleda et al, 2000;Cox et al, 2004). In vitro and in vivo studies in the last years have shown that these quiescent Ph þ HSCs are insensitive to imatinib mesylate treatment (Graham et al, 2002;Chu et al, 2005) and these cells have not been eliminated in Ph þ patients.…”
Section: Introductionmentioning
confidence: 99%